2013
DOI: 10.5999/aps.2013.40.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Onlay Rib Bone Graft in Elevation of Reconstructed Auricle: 17 Years of Experience

Abstract: BackgroundA cartilage wedge block and covering flap are standard procedures for firm elevation of the ear in microtia correction. However, using costal cartilage for elevation of the reconstructed auricle can be insufficient, and the fixed cartilage wedge block may be absorbed or may slip out. Furthermore, elevating covering flaps is time-consuming and uses up fascia, a potential source of reconstruction material. Therefore, we propose an innovative method using autologous onlay rib bone graft for auricular el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Many studies have reported a positive correlation between the surgical time and complication rate [18]. Costal cartilage harvesting is also accompanied by donor-site morbidities such as pneumothorax, hemothorax, atelectasis, infection, seroma, visible chest scars, and chronic postoperative pain [19]. Despite their low incidence, acute morbidities (e.g., pneumothorax, hemothorax, and atelectasis) can be life-threatening when appropriate care fails [20].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported a positive correlation between the surgical time and complication rate [18]. Costal cartilage harvesting is also accompanied by donor-site morbidities such as pneumothorax, hemothorax, atelectasis, infection, seroma, visible chest scars, and chronic postoperative pain [19]. Despite their low incidence, acute morbidities (e.g., pneumothorax, hemothorax, and atelectasis) can be life-threatening when appropriate care fails [20].…”
Section: Discussionmentioning
confidence: 99%
“…[12] Some authors consider cartilage as the graft of choice for orbitozygomatic reconstruction owing to its ease of carving a complex graft shape. [9] There is always a concern of bone resorption; however, Kim et al [13] and others reported that costal bone grafted on the facial area maintained its volume even after a 17-year follow-up of their case.…”
Section: Discussionmentioning
confidence: 99%